Computer Vision in Human-Computer Interaction ECCV 2006 Workshop on HCI, Graz, Austria, May 13, 2006, Proceedings - Huang, Thomas S.; Sebe, Nicu; Lew, Michael S.; Pavlovic, Vladimir; Kölsch, Mathias; Galata, Aphrodite; Kisacanin, Branislav (Image Processing, Computer Vision, Pattern Recognition, and Graphics ;, 2006)
The interests and goals of HCI (human-computer interaction) include understanding, designing, building, and evaluating complex interactive systems - involving many people and technologies. Developments in software and hardware technologies are continuously driving applications in supporting our collaborative and communicative needs as social beings, both at work and at play. At the same time, similar developments are pushing the human-computer interface beyond the desktop and into our pockets, streets, and buildings. Developments in mobile, wearable, and pervasive communications and computing technologies provide exciting challenges and opportunities for HCI. This volume presents the proceedings of the HCI 2006 Workshop, held in conjunction with ECCV 2006 (European Conference on Computer Vision) in Graz, Austria. The goal of this workshop was to bring together researchers from the field of computer vision whose work is related to human-computer interaction. The 11 papers presented in this volume were carefully reviewed and selected from 27 submissions. They address a wide range of theoretical and application issues in human-computer interaction. There were four thematic sessions named: face analysis; gesture and emotion recognition; event detection; and applications. .